Pengaruh Profitabilitas, Leverage, Loan To Asset Ratio Dan Beban Operasional Pendapatan Opersional (Bopo) Terhadap Tax Avoidance (Studi Pada Perusahaan Perbankan Yang Terdaftar Di Bei Tahun 2017-2020) - Rudy Anggriawan; Vivian Wijaya; Willie Anderson; Jessi Charina Sembiring (Jurnal AKMAMI (Akuntansi Manajemen Ekonomi), 2022)
The research approach used is a quantitative approach. The sampling method is purposive sampling, a sample of 13 banking companies listed on the Indonesia Stock Exchange in 2017-2020. The results show that return on assets, debt to equity ratio, loan to asset ratio, and operating expenses and operating income have a simultaneous and significant effect on the effective tax rate (Studies on banking companies listed on the Indonesia Stock Exchange in 2017-2020). Return to assets has a partial and significant effect on the effective tax rate (Studies on banking companies listed on the IDX in 2017-2020). Debt to equity ratio has no effect and is not partially significant on the effective tax rate (Study on banking companies listed on the IDX in 2017-2020). The loan to asset ratio has no effect and is not partially significant on the effective tax rate (Study on banking companies listed on the Indonesia Stock Exchange in 2017-2020). Operating expenses and operating income have no effect and are not partially significant on the effective tax rate (Study on banking companies listed on the IDX in 2017-2020)..